Attitudes of Cycle One School Teachers at the Basic Education Towards Training Courses "A Field Study in Lattakia City" - يوسف , آصف; زمرد , أميرة; حسين الحسين, فادية (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The current research aims to identify the attitudes of Cycle One school teachers at the basic education in Lattakia City towards training courses in terms of (cognitive dimension, emotional dimension, and behavioral dimension), which they underwent in 2019. The method used was descriptive and the tool was a questionnaire (which was prepared by the researcher and approved by specialists in the field of Education at Tishreen University, and the researcher studied its psychometric properties). It was applied to a sample of 138 teachers at Cycle One schools in Lattakia. The results of the research have shown that the attitudes of Cycle One teachers at the basic education in Lattakia towards training courses as a whole are positive. Moreover, the results have found that there are no differences in the attitudes of teachers twoards training courses according to the variables of gender and years of experience, in addition to the existence of differences in their attitudes towards training courses according to the educational qualification (for both university graduates and graduates of educational habilitation diploma) as well as according to the variable of the number of training courses (for teachers who have undergone two ones).